2019
DOI: 10.1038/s41467-019-09514-1
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced β-adrenergic signalling underlies an age-dependent beneficial metabolic effect of PI3K p110α inactivation in adipose tissue

Abstract: The insulin/IGF-1 signalling pathway is a key regulator of metabolism and the rate of ageing. We previously documented that systemic inactivation of phosphoinositide 3-kinase (PI3K) p110α, the principal PI3K isoform that positively regulates insulin signalling, results in a beneficial metabolic effect in aged mice. Here we demonstrate that deletion of p110α specifically in the adipose tissue leads to less fat accumulation over a significant part of adult life and allows the maintenance of normal glucose tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 52 publications
11
37
2
Order By: Relevance
“…In line with what is reported here in mouse 3T3-L1 adipocytes, parallel studies in our lab have revealed that genetic or pharmacological inactivation of p110α in the adipose tissue of mice results in enhanced adrenergic signalling, which promotes lipolysis and energy expenditure 19 . The enhancement in adrenergic signalling mitigates the effect of insulin resistance ensuing from p110α inactivation thus producing overall a lean phenotype and improved glucose homeostasis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with what is reported here in mouse 3T3-L1 adipocytes, parallel studies in our lab have revealed that genetic or pharmacological inactivation of p110α in the adipose tissue of mice results in enhanced adrenergic signalling, which promotes lipolysis and energy expenditure 19 . The enhancement in adrenergic signalling mitigates the effect of insulin resistance ensuing from p110α inactivation thus producing overall a lean phenotype and improved glucose homeostasis.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with upregulated mitochondrial function as result of p110α inhibition reported here, a recent study from our lab has demonstrated reduced age-dependent fat accumulation in mice with adipose tissue-specific p110α deletion using the adiponectin-Cre strain 19 . However, a previous study which used an aP2-Cre strain to delete p110α in the adipose tissue of mice has reported obesity and decreased energy expenditure 37 , which are diametrically different phenotypes from those reported in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, it is worth noting that previous studies have shown that this biological readout is not a good indicator of the actual insulin sensitivity of this tissue 64,65 . In fact, similar defects in the suppression of hepatic glucose production were found in loss-of-function mouse models for signaling elements of the insulin and IGF1 pathways in both skeletal muscle (IGF1, Akt family) and WAT (PI3Kα) 16,66,67 . Our analyses also indicated that Vav2 L332A/L332A animals exhibit lower rates of insulin-induced glucose clearance than controls ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 53%
“…Reduced adipose mass can reflect altered energy balance rather than lipodystrophy. Reduction of PI3K pathway activity by overexpression of the lipid phosphatase Pten in mice was previously reported to enhance energy expenditure via brown adipose tissue activation [ 41 ], albeit without IR, while pharmacological or genetic inhibition of the p110α catalytic subunit of PI3K has also been associated with increased energy expenditure [ [40] , [41] , [42] , [43] ]. Moreover, a similar energetic phenotype on brown adipose-specific knockout of Pik3r1 has recently been described [ 44 ].…”
Section: Discussionmentioning
confidence: 99%